Short-interfering RNA evaluation in experimental mice rabies virus infection caused by variant 2 and variant 3 - Appolinario, C. M.; Allendorf, S. D.; Peres, M. G.; Antunes, J. M. A. P.; Vicente, A. F.; Pantoja, J. C. F.; Megid, J. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Rabies is an ancient disease and until now no effective treatment is available. Treatment using short-interfering RNA (siRNA) to inhibit rabies virus (RABV) replication showed promising results in vitro. Our purpose was to evaluate the efficacy of siRNA in treating mice experimentally infected with different street RABV strains.